Transformasi Digital Desa melalui Aplikasi Web Terpadu: Integrasi E-commerce dan Sistem Manajemen Inventaris - Assabilla, Rahma; Rosya, Senna Bela; Al Rozaq, Muhammad Abdulloh; Riyanto, Joko (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Sukamukti Village, located in Tanjungmedar District, Sumedang Regency, is grappling with a severe digital divide that necessitates immediate attention. Consequently, the village faces significant challenges posed by limited technological infrastructure and inadequate community knowledge regarding internet utilization, largely attributed to low digital literacy rates. This predicament threatens to impede various aspects of village development, encompassing economic growth, education, and administrative governance. To address this issue, a proposed solution involves leveraging digital transformation to foster MSME development through the integration of e-commerce platforms and web-based applications. These solutions aim to enhance inventory management efficiency, improve public services, and promote transparency. Research findings indicate that community members have demonstrated improved comprehension of digital technology. Implementation of this application has yielded more effective inventory management, mitigating the risk of asset misappropriation and streamlining public administrative services provided by the village government. Furthermore, the development of e-commerce features has empowered local MSME stakeholders to market their products digitally, expand their customer base, and increase revenue.